Percepção de vulnerabilidade ao hiv/aids: um estudo exploratório com jovens em situação de rua - Lucena, Stefanny Karulayne Figueiredo de (2017)
This dissertation presented in an article format has as its general objective to analyze the vulnerability to HIV/AIDS with youthster on street conditions. Using as theoretical reference the theoretical model of vulnerability. The Specific goals are: to identify vulnerability aspects with youthsters on street conditions and assess if youthsters identify the street condition as a factor that can influence the rise of vulnerability. It is a cross-sectional study, with qualitative design, which has been conducted at the Centro de Referência Especializado para População em Situação de Rua (Centro POP). The sample, for convenience, possesses twenty youthsters, four female and sixteen male who are on street condition, aged between 18 to 24 years (M=21, SD=1,9). The instruments used were a semi-structured interview, a Questionnaire of Sexual and Vulnerability Practices, and a socio-demographic questionnaire. The socio-demographic data of the questionnaire of sexual practices and vulnerability have been analyzed by descriptive statistics. The interviews were transcribed and analyzed by thematic categorical analysis. The results indicates that street youthsters in street condition are exposed to vulnerability in its three dimensions, individual, social and programmatic. In the individual dimension, two categories emerged, entitled as the quality of information about HIV/AIDS and the other is the use of condoms in daily life. In this, the information about HIV transmission emerges as erroneous and scarce and the use of condoms arises in a contradictory way, being only necessary when there is not a relationship with emotional involvement. In the social dimension were identified the category street condition and vulnerability, fragility in affective and relationship bonds and street condition and drug use. The street situation appears as a context that increases vulnerability to HIV/AIDS. There seems to be a relationship of rupture between affective and relational attachments, drug use, and the street situation. In the programmatic dimension, the category called HIV/AIDS promotion and prevention practices in which are observed incipient actions without deepening of questions related to HIV/AIDS at the center wich the youthsters are users.